Painted steel plate

A coated steel sheet with a hot-dip Al-Zn-based plated steel sheet and specific coatings enhances adhesion and corrosion resistance at processed parts and cut edges, addressing the limitations of existing chromate-free technologies.

JP7618634B2Active Publication Date: 2025-01-21JFE GALVANIZING & COATING CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2022193164
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-12-01
Publication Date
2025-01-21
Estimated Expiration
2042-12-01

AI Technical Summary

Technical Problem

Existing coated steel sheets, particularly those without chromate, face insufficient corrosion resistance at processed parts and cut edges, and there is a risk of peeling between the chemical conversion treatment film and the primer paint film.

Method used

A coated steel sheet with a hot-dip Al-Zn-based plated steel sheet containing 50-60% Al, a chemical conversion coating containing epoxy resin and inorganic compounds like vanadium oxide, and a primer coating with epoxy resin having a urethane bond and specific inorganic compounds, ensuring strong adhesion and enhanced corrosion resistance.

Benefits of technology

The solution provides excellent adhesion and corrosion resistance at processed parts and cut edges, improving durability and reducing the risk of paint film peeling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618634000001
    Figure 0007618634000001
Patent Text Reader

Abstract

To provide a precoated steel sheet which has good adhesion between a chemically converted coating and a primer coating, and is excellent in corrosion resistance of a worked portion and a cut end.SOLUTION: A chemically converted coating includes a resin component and an inorganic compound, contains 30 to 54 mass% of an epoxy resin having a bisphenol skeleton as the resin component and 46 to 70 mass% of a vanadium oxide, a zirconium oxide and a fluorine compound in total as the inorganic compound, and a primer coating film includes a resin component and an inorganic compound, contains 40 to 88 mass% of an epoxy resin (e) having an urethane bod and a polyester resin (p) in total as the resin component, has a content mass ratio (e):(p) of the epoxy resin (e) and the polyester resin (p) of 80:20 to 60:40, and contains 4 to 20 mass% of the vanadium compound, 4 to 20 mass% of a phosphate compound and 4 to 20 mass% of a magnesium oxide as the inorganic compound.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a coated steel sheet which has good adhesion between a chemical conversion coating and a primer coating and which has excellent corrosion resistance at processed portions and cut edges. [Background technology]

[0002] Coated steel sheets, which are made by forming a chemical conversion coating and a primer coating on the surface of a steel sheet plated with zinc or an alloy containing zinc (hereinafter referred to as "zinc-based plated steel sheet"), and then forming various coatings on top of that, have many advantages, such as stable quality and streamlining by eliminating the need for a painting process at the customer's site. As such, they are widely used as exterior materials for the roofs and walls of buildings, interior materials such as partitions, and various components for electrical equipment products. Generally, such coated steel sheets are manufactured in coils, and after being cut to a predetermined size, they are subjected to various processes, including 90-degree or 180-degree bending by press forming, roll forming, or embossing, before being used. Therefore, the coated steel sheets are required to have long-term durability even in the cut and processed parts.

[0003] In order to meet these requirements, it has been common to apply a chemical conversion treatment containing chromate to a zinc-based plated steel sheet, form a primer coating containing a chromate-based rust-preventive pigment, and then form a top coating of a thermosetting polyester-based resin coating or, for requirements for higher weather resistance, a fluororesin coating to produce a painted steel sheet. However, in recent years, the use of chromate, which is an environmentally hazardous substance, has come to be viewed as problematic, and there is a strong demand for painted steel sheets that do not contain chromate, so many chromate-free painted steel sheets have been developed.

[0004] On the other hand, hot-dip Al-Zn-plated steel sheets such as 55% Al-Zn-plated steel sheets have good corrosion resistance but tend to have poor mechanical properties, particularly elongation properties. Therefore, when processed, such as bending, cracks may occur in the plating layer at the processed part depending on the degree of processing, which may cause deterioration of corrosion resistance due to the cracked parts, and may cause problems in use. In addition, in hot-dip Al-Zn-coated steel sheets with a high Al ratio, such as 55% Al-Zn-coated steel sheets, the Zn in the coating layer dissolves preferentially at the cut edges for sacrificial corrosion protection. However, because the ratio of Zn in the coating layer is low, the corrosion width from the cut edges tends to become larger in the early stages of corrosion.

[0005] To address such problems, for example, Patent Document 1 discloses a coated galvanized steel sheet in which a paint composition containing a non-chromate-based rust-preventive pigment such as a molybdenum compound in a primer coating is applied to the galvanized steel sheet via a chemical conversion coating. However, the applicable zinc-plated steel sheets are limited to those containing 94% or more zinc, and chromate is applied as the chemical conversion coating, so that the coated steel sheets cannot be said to be chromate-free.

[0006] Moreover, Patent Document 2 discloses a surface treatment agent (chemical conversion coating) made of a resin and a chromate-free rust-preventive pigment. Furthermore, Patent Document 3 discloses a painted zinc-based plated steel sheet that uses a surface treatment agent (chemical conversion coating) made of a resin and a chromate-free rust-preventive pigment. Furthermore, Patent Document 4 discloses a technology aimed at improving the overall rust prevention properties of a painted zinc-based plated steel sheet having a chemical conversion coating and a primer coating, both of which contain specific non-chromate rust-preventive pigments. However, all of the techniques disclosed in Patent Documents 2 to 4 have the problem that sufficient corrosion resistance, particularly corrosion resistance at bent portions and cut ends, cannot be obtained.

[0007] Therefore, there is a demand for technology related to chromate-free painted steel sheets that aims to improve the corrosion resistance, particularly of bent parts and cut ends. For example, Patent Document 5 discloses a technique for improving the corrosion resistance of processed portions and cut edges of a coated steel sheet comprising a zinc-based plated steel sheet, a chemical conversion coating, a primer coating, and a topcoat coating by adjusting the types and contents of the resin components and inorganic compounds that constitute the chemical conversion coating and the primer coating. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2008-291162 A [Patent Document 2] JP 2009-127057 A [Patent Document 3] JP 2014-214315 A [Patent Document 4] JP 2005-169765 A [Patent Document 5] JP 2016-176118 A Summary of the Invention [Problem to be solved by the invention]

[0009] However, in the technology of Patent Document 5, the chemical conversion coating and the primer coating have a common urethane bond, which improves adhesion and provides a certain degree of corrosion resistance in processed areas. However, the corrosion resistance in severely bent areas and cut edges is not sufficient, and further improvement is desired. Furthermore, with conventional coated steel sheets, there is a risk of peeling of the coating between the chemical conversion coating and the primer coating, and further improvement in the adhesion between the chemical conversion coating and the primer coating has been desired.

[0010] In view of these circumstances, the present invention has an object to provide a coated steel sheet that has good adhesion between a chemical conversion coating and a primer coating and that has excellent corrosion resistance in processed portions and cut edges, particularly on a base of a hot-dip Al-Zn-plated steel sheet containing 50 mass % or more of Al, from which excellent corrosion resistance can be expected. [Means for solving the problem]

[0011] The present inventors have conducted studies to solve the above-mentioned problems with respect to a coated steel sheet comprising: a hot-dip Al-Zn-plated steel sheet having a composition containing 50-60 mass% Al, 1-3 mass% Si, and 0-6 mass% of optional added components, with the balance being Zn and unavoidable impurities; a chemical conversion coating film that does not contain chromate-based compounds, formed on at least one side of the hot-dip Al-Zn-plated steel sheet; a primer coating film that does not contain chromate-based compounds, formed on the chemical conversion coating film; and a topcoat coating film formed on the primer coating film. As a result, it was found that by making the chemical conversion coating contain an epoxy resin component and an inorganic compound such as vanadium oxide in certain proportions, and by making the primer coating contain a certain proportion of an epoxy resin having urethane bonds and an inorganic compound such as a vanadium compound, the chemical conversion coating and primer coating are formed in a state containing a certain proportion of epoxy resin, which is a specific common element that maximizes corrosion resistance, and therefore it is possible to increase the adhesion between the chemical conversion coating and the primer coating and improve the corrosion resistance of processed parts and cut ends.

[0012] The present invention has been made based on the above findings, and the gist of the present invention is as follows. 1. A hot-dip Al-Zn plated steel sheet having a plating layer having a composition containing 50 to 60 mass% Al, 1 to 3 mass% Si, and optional added components: 0 to 6 mass%, with the balance being Zn and unavoidable impurities; a chemical conversion coating film that does not contain a chromate-based compound and is formed on at least one surface of the hot-dip Al-Zn-plated steel sheet; a primer coating film that does not contain a chromate-based compound and is formed on the chemical conversion coating film; A topcoat coating film formed on the primer coating film; A coated steel sheet comprising: the chemical conversion coating contains a resin component and an inorganic compound, the resin component containing 30 to 54 mass% of an epoxy resin having a bisphenol skeleton, and the inorganic compound containing 46 to 70 mass% in total of vanadium oxide, zirconium oxide, and a fluorine compound, The primer coating film contains a resin component and an inorganic compound, and contains, as the resin components, an epoxy resin (e) having a urethane bond and a polyester resin (p) in a total amount of 40 to 88 mass%, the content of the epoxy resin (e) and the polyester resin (p) is a mass ratio of (e):(p)=80:20 to 60:40, and contains, as the inorganic compounds, 4 to 20 mass% of a vanadium compound, 4 to 20 mass% of a phosphoric acid compound, and 4 to 20 mass% of magnesium oxide. A coated steel sheet.

[0013] 2. The coating weight of the chemical conversion coating is 0.025 to 0.5 g / m 2 2. The coated steel sheet according to item 1 above, characterized in that the thickness of the primer coating film is 3 to 10 μm.

[0014] 3. The coated steel sheet according to 1 or 2 above, characterized in that the content (e1% by mass) of the epoxy resin (e) having a urethane bond in the primer coating film and the content (e2% by mass) of the epoxy resin having a bisphenol skeleton in the chemical conversion coating film satisfy the relationship e1 / e2 = 0.7 to 1.5.

[0015] 4. The coated steel sheet according to any one of 1 to 3 above, characterized in that the chemical conversion coating contains, as the inorganic compounds, 2 to 10 mass% of the vanadium oxide, 36 to 60 mass% of the zirconium oxide, and 0.5 to 5 mass% of the fluorine compound, calculated as fluorine atoms.

[0016] 5. The micro Vickers hardness (JIS Z2244:2009) of the plating film is 60 to 100HV 0.01 5. The coated steel sheet according to any one of the above 1 to 4, characterized in that

[0017] 6. The coated steel sheet according to any one of the above 1 to 4, wherein the plating layer contains 1 to 5 mass % of Mg as the optional added component. Effect of the Invention

[0018] According to the present invention, it is possible to provide a coated steel sheet which has good adhesion between a chemical conversion coating and a primer coating and which has excellent corrosion resistance at processed portions and cut edges. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The coated steel sheet of the present invention comprises a hot-dip Al-Zn-plated steel sheet having a composition containing 50 to 60 mass% Al, 1 to 3 mass% Si, and 0 to 6 mass% of optional added components, with the balance being Zn and unavoidable impurities; a chemical conversion coating film that does not contain a chromate-based compound and is formed on at least one surface of the hot-dip Al-Zn-plated steel sheet; a primer coating film that does not contain a chromate-based compound and is formed on the chemical conversion coating film; A topcoat coating film formed on the primer coating film; It is a coated steel plate equipped with the above.

[0020] (Hot-dip Al-Zn coated steel sheet) The hot-dip Al-Zn plated steel sheet has a plating layer having a composition containing 50-60 mass% Al, 1-3 mass% Si, and 0-6 mass% optional added components, with the balance being Zn and unavoidable impurities. By having the plating layer of the hot-dip Al-Zn plated steel sheet have the above-mentioned composition, it is possible to form a dendritic phase and an interdendritic phase surrounding the dendritic phase in a network shape in the plating layer, thereby improving corrosion resistance.

[0021] Here, the Al content in the plating layer is 50 to 60 mass% from the viewpoint of the balance between corrosion resistance and operation. If the Al content of the plating layer is at least 50 mass%, the dendritic solidification of Al occurs sufficiently. As a result, the plating layer mainly contains Zn in a supersaturated state, and is composed of a portion where Al is solidified into dendrites (α-Al dendritic phase) and the remaining portion between the dendritic voids (interdendritic phase), and the dendritic phase is laminated in the thickness direction of the plating layer, thereby realizing a structure with excellent corrosion resistance. In addition, the corrosion resistance can be improved by the stable presence of a surface oxide film of Al on the surface of the plating layer. On the other hand, if the Al content in the plating layer exceeds 60 mass%, the content of Zn, which has a sacrificial anticorrosive effect on Fe, decreases, and the corrosion resistance deteriorates. For this reason, the Al content in the plating layer is set to 60 mass% or less. In addition, from the above-mentioned viewpoint, the Al content in the plating layer is preferably about 55 mass%.

[0022] In addition, the Si in the plating layer is added to the plating bath for the purpose of improving workability and corrosion resistance by suppressing the growth of an interface alloy layer formed at the interface with the base steel sheet. The interface alloy layer is hard and brittle, and if it grows too thick, it becomes the starting point of crack generation during processing, so it is preferable to make it as thin as possible. In the case of hot-dip Al-Zn-plated steel sheets, when the plating bath contains Si and hot-dip plating is performed, Fe on the steel sheet surface reacts with Al and Si in the bath to form an alloy consisting of Fe-Al and / or Fe-Al-Si compounds at the same time as the base steel sheet is immersed in the plating bath. The formation of this Fe-Al-Si-based interface alloy layer can suppress the growth of the interface alloy layer. And, when the Si content in the plating layer is 1% by mass or more, the growth of the interface alloy layer can be sufficiently suppressed. On the other hand, when the Si content in the plating layer exceeds 3% by mass, the plating layer is easily precipitated with a Si phase that reduces workability and becomes a cathode site. The precipitation of the Si phase can be suppressed by increasing the Mg content, but in that case, the manufacturing cost increases, the workability decreases due to the increase in the amount of Mg2Si, and the composition control of the plating bath becomes more difficult. For this reason, the Si content in the plating layer is set to 3 mass% or less. From the same viewpoint, the Si content in the plating layer is preferably 1 to 2 mass%.

[0023] The plating layer contains Zn as a component other than Al and Si. By containing Zn in the plating layer, a sacrificial corrosion protection effect can be obtained, and it becomes possible to improve the corrosion resistance.

[0024] Furthermore, the plating layer may contain 0 to 6 mass % of optional additive components in addition to the above-mentioned Al, Si, and Zn. The optional additive components can be appropriately selected depending on the performance required for the plating layer, and examples thereof include alkaline earth metals such as Ca and Mg, and additive components such as Mn, V, Cr, Mo, Ti, Sr, Ni, Co, Sb, W, Sn, and B. Although these optional components have the effect of improving the plating appearance and further improving corrosion resistance, there is a risk of reducing the workability of the plating layer. Therefore, the content of these optional components must be 6 mass% or less, and preferably 5 mass% or less.

[0025] In order to further improve the corrosion resistance of the cut end, the plating layer preferably contains 1 to 5 mass% of Mg among the optional additives. When the plating layer corrodes, Mg is contained in the corrosion product, and the stability of the corrosion product precipitated on the exposed steel surface of the cut end is improved, and the progress of corrosion is delayed, resulting in an effect of further improving the corrosion resistance of the cut end. In the present invention, since Mg is also contained in the primer coating, such an effect becomes more remarkable. This is because the stability of the corrosion product is improved and the corrosion of the plating is suppressed by continuously supplying Mg from the primer. By making the content of Mg 1 mass% or more, a sufficient corrosion retardation effect is obtained, while by making the content of Mg 5 mass% or less, the workability is not significantly reduced, and the corrosion resistance of the processed part can be maintained at a high level. From the same viewpoint, the content of Mg in the plating layer is more preferably 2 to 5 mass%, and even more preferably 3 to 5 mass%.

[0026] The plating layer contains components of the base steel sheet that are incorporated into the plating layer as a result of a reaction between the plating bath and the base steel sheet during plating treatment, as well as unavoidable impurities in the plating bath. The coating layer may contain up to about 2 mass % of Fe as a component of the base steel sheet. Types of unavoidable impurities in the coating bath include, for example, Fe, Cu, and the like. Regarding Fe in the coating layer, it is not possible to distinguish between Fe taken in from the base steel sheet and Fe in the coating bath and quantify the same. The total content of unavoidable impurities is not particularly limited, but from the viewpoint of maintaining the corrosion resistance and uniform solubility of the coating, the total amount of unavoidable impurities excluding Fe is preferably 1 mass% or less.

[0027] The means for forming the coating layer on the base steel sheet is not particularly limited, and a normal continuous hot-dip galvanizing facility can be used. For example, the base steel sheet is heated to a predetermined temperature in an annealing furnace maintained in a reducing atmosphere, and after annealing, rolling oil and the like adhering to the steel sheet surface are removed and an oxide film is reduced and removed, the steel sheet is immersed in a hot-dip galvanizing bath containing a predetermined concentration of optional additive components such as Al, Zn, Si, and Mg through a snout whose lower end is immersed in the coating bath. The steel sheet immersed in the coating bath is then pulled up above the coating bath via a sink roll, and the coating amount is adjusted by spraying pressurized gas from a gas wiping nozzle arranged above the coating bath toward the surface of the steel sheet, and then cooled by a cooling device to form a coating layer.

[0028] In order to further improve the corrosion resistance of the processed portion, the hot-dip Al-Zn-plated steel sheet preferably has a flexible plating layer. Specifically, the micro Vickers hardness (JIS Z2244:2009) of the plating layer is preferably 60 to 100 HV. 0.01 It is preferable that the micro Vickers hardness of the plating layer is 60 to 100 Hv. 0.01 By making the hardness small, the workability of the coated steel sheet is improved, the generation of cracks in the plating layer in the processed area is suppressed, and the corrosion resistance after processing can be further improved. In the present invention, since the resin components of the primer coating film contain an epoxy resin having a urethane bond and a polyester resin in a specified ratio, this effect becomes even more remarkable. This is because the primer coating film has excellent workability, and therefore cracks in the plating layer in the processed area are reduced, thereby preventing cracks from generating in the primer coating film. The micro Vickers hardness of the plating layer is 100Hv 0.01 If the Vickers hardness of the plating layer exceeds 60 Hv, there is a risk that sufficient workability cannot be obtained. 0.01 If the hardness is less than 60 Hv, the scratch resistance of the plating layer surface may be reduced. 0.01 It is more preferable that: The micro Vickers hardness was measured using a test force of 10 g (Hv 0.01 ) testing is being carried out.

[0029] Such a highly workable coating layer can be produced, for example, by heat treatment at 200°C for 24 hours, and the limit elongation of the hot-dip Al-Zn coated steel sheet before heat treatment can be improved to a maximum of 25%. This is thought to be because the Zn that is supersaturated in solid solution in the aluminum-rich dendritic phase is expelled by the heat treatment, softening the coating layer.

[0030] (chemical conversion coating) In the coated steel sheet of the present invention, a chemical conversion coating film not containing a chromate compound is formed on at least one side of the hot-dip Al-Zn-plated steel sheet. By forming the chemical conversion coating film between the hot-dip Al-Zn-plated steel sheet and the primer coating film, it is possible to improve adhesion to the primer coating film and further improve the corrosion resistance of the coated steel sheet.

[0031] The chemical conversion coating contains a resin component and an inorganic compound, and the resin component contains 30 to 54 mass% of an epoxy resin having a bisphenol skeleton, and the inorganic compound contains 46 to 70 mass% in total of vanadium oxide, zirconium oxide, and a fluorine compound. The chemical conversion coating is composed of a resin component and an inorganic compound, and by adjusting the content of the resin component and optimizing the type and content of the inorganic compound, high corrosion resistance can be achieved. In addition, the adhesion to the primer coating described below can be improved, and the corrosion resistance of the processed part can be improved.

[0032] The resin component used is a resin in which an epoxy resin having a bisphenol skeleton is dispersed in water. By forming a loose bond with the epoxy resin in the primer coating film described below through hydrogen bonds or the like, the adhesion between the primer and the chemical conversion coating film is very excellent. Such an effect cannot be obtained with acrylic resins, polyester resins, etc.

[0033] The resin component is contained in the chemical conversion coating in an amount of 30 to 54 mass %. If the content of the resin component in the chemical conversion coating is less than 30 mass %, the binder effect of the chemical conversion coating is insufficient, whereas if the content of the resin component in the chemical conversion coating exceeds 54 mass %, the functions of the inorganic components described below, such as the inhibitor action, become insufficient.

[0034] The resin component in the chemical conversion coating is an epoxy resin having a bisphenol skeleton. By using an epoxy resin having a bisphenol skeleton, very good corrosion resistance and adhesion can be obtained. The resin component acts as a binder for the chemical conversion coating, and the epoxy resin has the effect of improving adhesion between the underlying aluminum-zinc alloy plated steel sheet and the upper primer coating. The epoxy resin having a bisphenol skeleton may be a known resin, and a chemical conversion treatment liquid may be obtained by dispersing the resin in a liquid such as water by a known method.

[0035] The inorganic compounds in the chemical conversion coating include at least vanadium oxide, zirconium oxide, and a fluorine compound. By including these inorganic compounds, the corrosion resistance, strength, processability, etc. of the chemical conversion coating can be improved.

[0036] Here, the total content of the vanadium oxide, the zirconium oxide, and the fluorine compound in the chemical conversion coating is 46 to 70 mass%. By containing the inorganic compounds in such a range, the corrosion resistance, strength, etc. of the chemical conversion coating can be improved without deteriorating other physical properties such as workability. From the same viewpoint, the total content of the vanadium oxide, the zirconium oxide, and the fluorine compound in the chemical conversion coating is preferably 46 to 65 mass%, and more preferably 46 to 57 mass%.

[0037] The vanadium oxide acts as a rust inhibitor in the chemical conversion coating. Examples of vanadium compounds added to the chemical conversion coating solution to generate vanadium oxide in the chemical conversion coating include vanadium pentoxide, metavanadic acid, ammonium metavanadate, vanadium oxytrichloride, vanadium trioxide, vanadium dioxide, magnesium vanadate, vanadyl acetylacetonate, and vanadium acetylacetonate. In particular, it is preferable to use a pentavalent vanadium compound or a trivalent or tetravalent vanadium compound obtained by reducing a pentavalent vanadium compound.

[0038] The content of vanadium oxide in the chemical conversion coating is not particularly limited, but is preferably 2 to 10 mass%. If the oxide of the vanadium compound is less than 2 mass%, the inhibitor effect decreases, leading to a decrease in corrosion resistance, and if the content of the vanadium oxide exceeds 10 mass%, there is a risk of the moisture resistance of the chemical conversion coating being decreased. From the same viewpoint, the content of vanadium oxide in the chemical conversion coating is more preferably 4 to 10 mass%, and even more preferably 6 to 10 mass%.

[0039] The zirconium oxide forms a dense film, which enhances the strength and corrosion resistance of the chemical conversion coating, as well as enhancing adhesion to the plating layer, thereby contributing to improved coverage and barrier effect. Examples of zirconium compounds added to the chemical conversion solution to generate zirconium oxide in the chemical conversion coating include neutral salts such as zirconium sulfate, zirconium carbonate, zirconium nitrate, zirconium lactate, zirconium acetate, and zirconium chloride. The content of zirconium oxide in the chemical conversion coating is not particularly limited, but is preferably 36 to 60 mass%. If the content of zirconium oxide is less than 36 mass%, the strength and corrosion resistance of the chemical conversion coating will decrease, and if the content of zirconium oxide is more than 60 mass%, the chemical conversion coating will become embrittled and may break or peel off when subjected to severe processing. From the same viewpoint, the content of zirconium oxide in the chemical conversion coating is more preferably 38 to 54 mass%, and more preferably 38 to 50 mass%.

[0040] The fluorine compound is added to the chemical conversion treatment liquid and acts as an adhesive agent for the hot-dip Al-Zn-plated steel sheet. As the fluorine compound, for example, fluoride salts such as ammonium salts, sodium salts, potassium salts, or fluorine compounds such as ferrous fluoride and ferric fluoride can be used. In particular, it is preferable to use fluoride salts such as ammonium fluoride, sodium fluoride, and potassium fluoride. Note that the fluorine compound added to the chemical conversion treatment liquid may be decomposed or react with other compounds due to drying or aging, and may exist in the chemical conversion treatment film as a fluorine compound different from the fluorine ion or the fluorine compound added to the chemical conversion treatment liquid. The content of the fluorine compound in the chemical conversion coating is not particularly limited, but is preferably 0.5 to 5 mass% in terms of fluorine atoms. If the content is less than 0.5 mass%, sufficient adhesion cannot be obtained at the processed portion, and if the content of the fluorine compound exceeds 5 mass%, the moisture resistance of the chemical conversion coating may decrease. From the same viewpoint, the content of the fluorine compound in the chemical conversion coating is more preferably 0.7 to 3 mass%.

[0041] The preferred coating weight of the chemical conversion coating is 0.025 to 0.5 g / m 2 The coating weight of the chemical conversion coating is 0.025 g / m 2 If the coating weight is less than 0.5 g / m, there is a risk of a decrease in adhesion to the underlying hot-dip Al-Zn plated steel sheet and the upper primer coating film, and a decrease in corrosion resistance.2 If the coating weight exceeds 0.05 to 0.2 g / m, the chemical conversion coating film is likely to break (peel off) when subjected to severe bending, and the corrosion resistance of the processed part may decrease. 2 It is more preferable that:

[0042] The chemical conversion coating is obtained by continuously applying a chemical conversion solution to the hot-dip Al-Zn-plated steel sheet using a roll coater or the like, and then drying the sheet at a peak metal temperature (PMT) of about 60 to 200° C. using hot air, induction heating, etc. These chemical conversion coatings may be single-layered or multi-layered, and in the case of multi-layered, multiple chemical conversion treatments may be performed sequentially.

[0043] (Primer coating) The coated steel sheet of the present invention further comprises a primer coating film that does not contain a chromate-based compound and is formed on the chemical conversion coating film. By forming a primer coating film on the chemical conversion coating, the adhesion between the chemical conversion coating film and the topcoat coating film described below can be further increased, and the corrosion resistance and rust prevention properties can be further improved.

[0044] The primer coating film contains a resin component and an inorganic compound, and contains, as the resin components, a total of 40 to 88 mass% of an epoxy resin (e) having a urethane bond and a polyester resin (p), the content of the epoxy resin (e) and the polyester resin (p) being in a mass ratio of (e):(p)=80:20 to 60:40, and contains, as the inorganic compounds, 4 to 20 mass% of a vanadium compound, 4 to 20 mass% of a phosphate compound, and 4 to 20 mass% of magnesium oxide. The primer coating film is composed of a resin component and an inorganic compound, and the resin component contains a specific range of epoxy resin and polyester resin having a urethane bond, and the type and content of the inorganic compound are optimized, thereby realizing excellent corrosion resistance and edge corrosion resistance. Also, the adhesion with the chemical conversion coating film can be increased, and the corrosion resistance of the processed part can be improved.

[0045] The epoxy resin (e) having a urethane bond has both flexibility and strength, and therefore improves the workability of the primer coating film and can suppress cracks in the primer coating film when processed. In addition, since the affinity with the chemical conversion coating film containing the epoxy resin is very high, the adhesion with the chemical conversion coating film is improved, and excellent corrosion resistance of edges and processed parts can be realized.

[0046] Furthermore, in the present invention, the relationship between the epoxy resin ratio in the chemical conversion coating and the epoxy resin ratio in the primer resin was investigated, and it was found that better performance can be achieved when the ratio is within a certain range. Specifically, assuming that the content of the epoxy resin having a urethane bond in the primer coating film (e1 mass %) and the content of the epoxy resin having a bisphenol skeleton in the chemical conversion coating film (e2 mass %), it is preferable for e1 / e2 to be in the range of 0.7 to 1.5, in order to achieve better interlayer adhesion and corrosion resistance.

[0047] In the primer coating, the epoxy resin (e) having urethane bonds is further mixed with a polyester resin (p), thereby improving the workability and flexibility of the primer coating, and improving the corrosion resistance of the processed part. Such an effect cannot be achieved with a primer film using another resin as the base polymer. For example, melamine resin has excellent density, but is poor in workability, so sufficient corrosion resistance of the processed part may not be obtained.

[0048] As the epoxy resin (e) having a urethane bond, a known resin such as a resin obtained by reacting a bisphenol type epoxy resin or a modified epoxy resin with a diisocyanate or polyisocyanate having two or more isocyanate groups can be used. The bisphenol type epoxy resin includes a bisphenol A type epoxy resin synthesized from bisphenol A and epichlorohydrin, and a bisphenol F type epoxy resin synthesized from bisphenol F and epichlorohydrin. From the viewpoint of corrosion resistance, it is preferable to use the bisphenol A type epoxy resin. The modified epoxy resin is obtained by modifying all or part of the epoxy groups or hydroxyl groups of the epoxy resin through a reaction with a modifying agent. Examples of the modifying agent used to modify the epoxy resin include polyester, alkanolamine, caprolactone, isocyanate compound, phosphoric acid compound, acid anhydride, etc. These modifying agents can be used alone or in combination of two or more.

[0049] The number average molecular weight of the epoxy resin (e) having a urethane bond is preferably 400 to 10,000, more preferably 400 to 9,000, and even more preferably 400 to 8,000, from the viewpoints of processability, corrosion resistance, coating workability, etc. The value of the number average molecular weight in the present invention can be obtained by gel permeation chromatography (GPC) using polystyrene as a standard substance. The epoxy equivalent of the epoxy resin (e) having a urethane bond is not particularly limited, but can be, for example, 180 to 5,000.

[0050] Examples of the diisocyanate or polyisocyanate compound having two or more isocyanate groups include aliphatic diisocyanates such as hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, and dimer acid diisocyanate, aromatic diisocyanates such as xylylene diisocyanate (XDI), metaxylylene diisocyanate, tolylene diisocyanate (TDI), and 4,4-diphenylmethane diisocyanate (MDI), and further cyclic aliphatic diisocyanates such as isophorone diisocyanate, hydrogenated XDI, hydrogenated TDI, and hydrogenated MDI, as well as adducts, biurets, and isocyanurates thereof. These polyisocyanate compounds can be used alone or in combination of two or more.

[0051] The polyester resin (p) can be obtained by a known method utilizing a dehydration condensation reaction between a polyhydric alcohol component and a polybasic acid component.

[0052] The polyhydric alcohols include glycols and trihydric or higher polyhydric alcohols. Examples of glycols include ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, polyethylene glycol, polypropylene glycol, neopentyl glycol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 2-butyl-2-ethyl-1,3-propanediol, methylpropanediol, cyclohexanedimethanol, and 3,3-diethyl-1,5-pentanediol. Examples of trihydric or higher polyhydric alcohols include glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, and dipentaerythritol. These polyhydric alcohols can be used alone or in combination of two or more.

[0053] As for the polybasic acid, a polyvalent carboxylic acid is usually used, but if necessary, a monovalent fatty acid or the like can be used in combination. Examples of polyvalent carboxylic acids include phthalic acid, terephthalic acid, tetrahydrophthalic acid, hexahydrophthalic acid, 4-methylhexahydrophthalic acid, bicyclo[2,2,1]heptane-2,3-dicarboxylic acid, trimellitic acid, adipic acid, sebacic acid, succinic acid, azelaic acid, fumaric acid, maleic acid, itaconic acid, pyromellitic acid, dimer acid, and the like, and their acid anhydrides, as well as 1,4-cyclohexanedicarboxylic acid, isophthalic acid, tetrahydroisophthalic acid, hexahydroisophthalic acid, hexahydroterephthalic acid, and the like. These polybasic acids can be used alone or in combination of two or more.

[0054] The primer coating contains, as the resin components, 40 to 88% by mass in total of the epoxy resin (e) having a urethane bond and the polyester resin (p). If the total content of the epoxy resin (e) having a urethane bond and the polyester resin (p) in the primer coating is less than 40% by mass, the binder function of the primer coating decreases, resulting in poor processability, whereas if it exceeds 88% by mass, the inhibitor action of the inorganic substances described below becomes insufficient.

[0055] In the primer coating, the content of the epoxy resin (e) and the polyester resin (p) is, in mass ratio, (e):(p)=80:20 to 60:40. If the ratio of the epoxy resin (e) having a urethane bond is less than 60:40, the flexibility becomes insufficient and the corrosion resistance of the processed part may decrease, and if the ratio of the polyester resin (p) is less than 80:20, the processability decreases. From the same viewpoint, it is preferable that the content of the epoxy resin (e) and the polyester resin (p) is, in mass ratio, (e):(p)=76:24 to 64:36.

[0056] The vanadium compound contained as the inorganic compound acts as an inhibitor. Examples of the vanadium compound include vanadium pentoxide, metavanadic acid, ammonium metavanadate, vanadium oxytrichloride, vanadium trioxide, vanadium dioxide, magnesium vanadate, vanadyl acetylacetonate, vanadium acetylacetonate, etc. Among these, it is particularly preferable to contain a pentavalent vanadium compound, or a trivalent or tetravalent vanadium compound obtained by reducing a pentavalent vanadium compound.

[0057] The vanadium compound contained in the primer coating film may be the same or different from the vanadium compound contained in the chemical conversion coating film. It is believed that the vanadate compound forms a highly adhesive passive film by reacting vanadate ions, which are gradually dissolved by moisture entering from the outside, with ions on the surface of the aluminum-zinc alloy plated steel sheet, thereby protecting the exposed metal parts and exerting a rust-preventing effect. In particular, this effect is more pronounced as the aluminum content in the plating layer increases, so that an extremely excellent effect can be exhibited by using an Al-Zn alloy plated steel sheet with a high aluminum content as the base.

[0058] The vanadium compound content in the primer coating film is 4 to 20% by mass. If the vanadium compound content in the primer coating film is less than 4% by mass, the inhibitor effect is reduced, resulting in reduced corrosion resistance, whereas if it exceeds 20% by mass, the moisture resistance of the primer coating film is reduced. From the same viewpoint, the vanadium compound content in the primer coating film is preferably 6 to 16% by mass.

[0059] The phosphate compound contained as the inorganic compound also acts as an inhibitor. As the phosphate compound, ammonium salt of phosphoric acid, alkali metal salt of phosphoric acid, alkaline earth metal salt of phosphoric acid, etc. can be used. Among these, alkali metal salt of phosphoric acid such as calcium phosphate is particularly preferably used. The phosphate compound is considered to form a stable corrosion product together with zinc ions and aluminum ions eluted from the aluminum-zinc alloy plated steel sheet due to corrosion, thereby protecting the exposed metal parts and inhibiting corrosion.

[0060] The content of the phosphoric acid compound in the primer coating film is 4 to 20% by mass. If the content of the phosphoric acid compound in the primer coating film is less than 4% by mass, the inhibitor effect decreases, resulting in a decrease in corrosion resistance, while if the content of the phosphoric acid compound in the primer coating film is more than 20% by mass, the moisture resistance of the primer coating film decreases. From the same viewpoint, the content of the phosphoric acid compound in the primer coating film is preferably 6 to 16% by mass.

[0061] The magnesium oxide contained as the inorganic compound has the effect of stabilizing the corrosion products generated during the initial corrosion as sparingly soluble magnesium salts. The amount of magnesium oxide added in the primer coating is 4 to 20% by mass. If the amount of magnesium oxide added in the primer coating is less than 4% by mass, the above effects are reduced, resulting in a decrease in corrosion resistance, whereas if the amount of magnesium oxide added in the primer coating is more than 20% by mass, the flexibility of the primer coating decreases, resulting in a decrease in corrosion resistance, particularly in the processed portion. From the same viewpoint, the content of magnesium oxide in the primer coating is preferably 4 to 10% by mass.

[0062] The crosslinking agent used in forming the primer coating film reacts with an epoxy resin having a urethane bond to form a crosslinked coating film, and is preferably a blocked polyisocyanate compound. Examples of the blocked polyisocyanate include polyisocyanate compounds in which the isocyanate group is blocked with alcohols such as butanol, oximes such as methyl ethyl ketoxime, lactams such as ε-caprolactams, diketones such as acetoacetic acid diester, imidazoles such as imidazole and 2-ethylimidazole, or phenols such as m-cresol.

[0063] The thickness of the primer coating is preferably 3 to 10 μm. If the thickness is thinner than this, it may cause a decrease in corrosion resistance and a decrease in adhesion to the chemical conversion coating and the topcoat coating. From the same viewpoint, the thickness of the primer coating is more preferably 5 μm or more. If the thickness of the primer coating is too thick, it may cause a decrease in manufacturing cost and processability, so it is preferably 10 μm or less.

[0064] The primer coating resin composition may contain various known components that are commonly used in the coating field, as necessary. Examples of known components include various surface conditioners such as leveling agents and defoamers, various additives such as dispersants, anti-settling agents, ultraviolet absorbers, light stabilizers, silane coupling agents, and titanate coupling agents, various pigments such as color pigments, extender pigments, and heat-shielding pigments, luster materials, curing catalysts, and organic solvents.

[0065] There is no particular restriction on the method of applying the coating composition to form the primer coating film, but it is preferable to apply the coating composition by a method such as roll coater coating or curtain flow coating. After applying the coating composition, the primer coating film is obtained by baking the coating composition by a heating means such as hot air heating, infrared heating, or induction heating. The baking process is usually performed at a maximum plate temperature of about 180 to 270°C for about 30 seconds to 3 minutes in this temperature range.

[0066] (Topcoat) The coated steel sheet of the present invention further comprises a topcoat coating film formed on the above-mentioned primer coating film. By forming the topcoat coating film, it is possible to impart a beautiful appearance and also to improve various performances such as processability, weather resistance, chemical resistance, stain resistance, water resistance, and corrosion resistance.

[0067] Examples of the resin component constituting the topcoat coating film include polyester-based resins, silicon polyester-based resins, polyurethane-based resins, acrylic-based resins, and fluororesins. In particular, from the standpoints of processability, corrosion resistance, and weather resistance, it is preferable that the coating film contains a fluororesin.

[0068] The topcoat coating film may contain appropriate amounts of the following additives depending on the purpose and use: titanium oxide, composite oxides, red iron oxide, carbon black, and other various coloring pigments; metallic pigments such as aluminum powder and coated mica; heat-shielding pigments; extender pigments such as mica, carbonates, and sulfates; various microparticles such as silica microparticles, nylon resin beads, and acrylic resin beads; curing catalysts such as p-toluenesulfonic acid and dibutyltin dilaurate; wax; leveling agents; defoamers; dispersants; anti-settling agents; ultraviolet absorbers; light stabilizers; anti-fouling agents; and other additives.

[0069] The thickness of the topcoat coating is not particularly limited, and can be appropriately adjusted depending on the required performance. For example, from the viewpoint of obtaining better corrosion resistance of the end and processed parts without deteriorating productivity, the thickness of the topcoat coating film is preferably 5 to 30 μm, more preferably 10 to 20 μm, and even more preferably 14 to 18 μm. When the thickness of the topcoat coating film is 5 μm or more, better corrosion resistance of the end and processed parts can be realized, while when it is 30 μm or less, the manufacturing process becomes complicated and the manufacturing cost does not increase.

[0070] The method of applying the coating composition for forming the topcoat coating film is not particularly limited. For example, the coating composition that is the material for the topcoat coating film can be applied by a method such as roll coater coating or curtain flow coating. After applying the coating composition, the topcoat coating film can be formed by baking using a heating means such as hot air heating, infrared heating, or induction heating. The baking temperature is usually set to a maximum plate temperature of about 180 to 270°C, and the baking process is performed within this temperature range for about 30 seconds to 3 minutes. EXAMPLES

[0071] <Coated steel sheet samples 1-50> Each sample of coated steel sheet was produced according to the following conditions: (1) hot-dip galvanized steel sheet, (2) chemical conversion coating, (3) primer coating, and (4) top coating.

[0072] (1) Hot-dip galvanized steel sheet The following hot-dip galvanized steel sheets were used. The types of coating used for each sample are shown in Table 1. Plating type 1: Sheet thickness 0.35 mm, plating coverage 80 g / m per side 2 Hot-dip Al-Zn-plated steel sheet (JIS G3321, AZ150) with a plating layer having a composition of Zn-55%Al Plating type 2: Sheet thickness 0.35 mm, plating coverage 80 g / m per side 2 Hot-dip Al-Zn-coated steel sheets (JIS G3321, AZ150) with a coating layer having a composition of Zn-55%Al were heat-treated in an atmosphere of 200°C for 4 hours after the coating layer was formed. Plating type 3: Sheet thickness 0.35 mm, plating coverage 80 g / m per side 2 , hot-dip Al-Zn-plated steel sheet having a plating layer having a composition of Zn-55%Al-4%Mg-2%Si Plating type 4: Sheet thickness 0.35 mm, plating coverage 130 g / m per side 2 , Hot-dip Zn-Al-plated steel sheet (JISG3317, Y25) with a plating layer having a composition of Zn-5%Al Plating type 5: Sheet thickness 0.35 mm, plating coverage 130 g / m per side2 Hot-dip Zn-coated steel sheet (JIS G3312, Z25) In addition, the micro Vickers hardness (JIS Z2244:2009) of each plated steel sheet was measured, and the results are shown in Table 1.

[0073] (2) Chemical conversion coating The resin component (A) in the chemical conversion coating was "Yukaresin RE-1050," an epoxy resin with a bisphenol skeleton manufactured by Yoshimura Oil Chemical Co., Ltd. The other resin components used were an acrylic resin (B) and a polyester resin (C). As the vanadium compound, an organic vanadium compound chelated with acetylacetone was used, as the zirconium compound, ammonium zirconium carbonate was used, and as the fluorine compound, ammonium fluoride was used. These raw materials were mixed to obtain a chemical conversion treatment solution. The pH of the chemical conversion treatment solution was set to 8 to 10. The content of each component in the chemical conversion treatment film was as shown in Table 1. For comparison, samples 49 and 50 were subjected to a chromate-based chemical conversion treatment (silica-containing coating-type chromate). The obtained chemical conversion treatment solution was applied to a hot-dip galvanized steel sheet using a roll coater and dried at a steel sheet temperature of 90°C for a baking time of 10 seconds to form a chemical conversion treatment film with the adhesion amount shown in Table 1.

[0074] (3) Primer coating The resin components of the primer coating film were: (e) a bisphenol A type epoxy resin (trade name "jER 1009", manufactured by Mitsubishi Chemical Corporation), which is an epoxy resin having a urethane bond, reacted with a blocked polyisocyanate compound (trade name "Desmodur BL-3175", manufactured by Sumika Bayer Urethane Co., Ltd.) in a mass ratio of 85:15; (d) a mixture of polyester resin (p) produced by the method described below, in the ratio shown in Table 1; or (e) a modified epoxy resin (trade name "Epiclon H-304-40", manufactured by DIC Corporation), which is an epoxy resin having a urethane bond, reacted with a blocked polyisocyanate compound (trade name "Desmodur BL-3175", manufactured by Sumika Bayer Urethane Co., Ltd.) in a mass ratio of 85:15; and (e) a mixture of polyester resin (p) produced by the method described below, in the ratio shown in Table 1. On the other hand, in other samples, urethane-cured polyester resin (F), melamine-cured polyester resin (G), and urethane-cured epoxy resin (H), which are resins outside the present invention, were used. In addition, magnesium vanadate was used as the vanadium compound of the rust-preventive pigment, and calcium phosphate was used as the phosphate compound. After adding the solvent and anti-rust pigment to the above components, 0.3 parts of dibutyltin dilaurate (DBTDL) was added as a reaction catalyst and mixed uniformly to produce a chrome-free primer coating paint. The coating composition of each sample is shown in Table 1. However, for samples 49 and 50, a primer coating containing 25% by mass of strontium chromate was used. The obtained primer coating paint was applied onto the chemical conversion coating film using a roll coater and baked at a steel plate temperature of 220°C for a baking time of 35 seconds to form a coating film with the thickness shown in Table 1 after baking.

[0075] Manufacture of polyester resin (p) The polyester resin (p) was produced as follows. In a flask equipped with a stirrer, a distillation column, a water separator, a cooling tube and a thermometer, 320 parts by mass of isophthalic acid, 200 parts by mass of adipic acid, 60 parts by mass of trimethylolpropane and 420 parts by mass of cyclohexanedimethanenol were charged, heated and stirred, and the temperature was raised from 160 ° C to 230 ° C at a constant rate over 4 hours while distilling the generated condensation water out of the system. When the temperature was raised to 230 ° C, 20 parts by mass of xylene was gradually added, and the condensation reaction was continued while maintaining the temperature at 230 ° C. The reaction was terminated when the acid value became 5 or less, and after cooling to 100 ° C, 120 parts by mass of Solvesso 100 (trade name, high boiling point aromatic hydrocarbon solvent manufactured by Exxon Mobil Corporation) and 100 parts by mass of butyl cellosolve were added to obtain a solution of polyester resin (p).

[0076] (4) Topcoat As the topcoat coating film, the following topcoat coating paint was used. I: Organosol-based baked fluororesin paint "Precolor No. 8800HR" (blue) (manufactured by BASF Japan Ltd.) with a mass ratio of polyvinylidene fluoride and acrylic resin of 80:20 II: Melamine-cured polyester paint (white) "Precolor HD0030HR" (BASF Japan Ltd.) The above topcoat paint was applied onto the undercoat with a roll coater, and in I, the steel plate was baked at a temperature of 260°C for a baking time of 40 seconds, and in II, the steel plate was baked at a temperature of 230°C for a baking time of 30 seconds, to form a coating film so that the film thickness after baking was as shown in Table 1.

[0077] <Evaluation> Each of the coated steel sheet samples obtained as described above was evaluated as follows. The evaluation results are shown in Table 1.

[0078] (1) Corrosion resistance of bent parts Each sample was subjected to a 5T bending (five sheets of the same plate as the test piece were sandwiched inside and bent at 180 degrees), and then subjected to a 240 cycle (total of 1920 hours) test in accordance with the JIS H8502 8.1 complex cyclic corrosion test, and the surface of the bent area was observed. The evaluation was based on the surface area ratio (%) of the topcoat film where blisters or white rust occurred, according to the following criteria. Results ranging from ⊚ to ◯ were considered to be acceptable. ◎◎: No blistering or rusting is observed. ◎: Swelling and / or rust is observed on 10% or less in total ○: Blisters and / or rust are observed, with a total of more than 10% and up to 20%. △: Blisters and / or rust are observed on a total of more than 20% and up to 50%. ×: Blisters and / or rust are observed on more than 50% in total.

[0079] (2) Corrosion resistance of cut ends For each sample, the end portion where the burr on the cut surface was on top (so-called upper burr) was subjected to a 240 cycle test (total of 1,920 hours) in accordance with the cyclic corrosion test (JIS H8502 8.1), and then the maximum width (mm) of blister or white rust at the end portion was measured. The evaluation was performed according to the following criteria. A result of ◎◎ to ○ was considered to be a pass. ◎◎: Maximum width is less than 3 mm ◎: Maximum width is 3mm or more and less than 5mm ○: Maximum width is 5mm or more and less than 8mm △: Maximum width is 8mm or more and less than 15mm ×: Maximum width is 15mm or more

[0080] (3) Adhesion at bent parts Each sample was bent at 1T (a sheet of the same material as the test specimen was sandwiched inside and bent at 180 degrees), immersed in boiling water for 2 hours, and then left indoors for 1 hour. After that, a forced coating peeling test was performed by applying cellophane tape (made by Nichiban) to the bent part and then immediately peeling it off. The evaluation was based on the percentage of peeled area of ​​the coating film after the coating peeling test. ⊚ and ◯ are considered to be pass. ◎: No peeling ○: Peeling area is less than 3% △: Peeling area is 3% or more but less than 10% ×: Peeling area is 10% or more

[0081] (4) Scratch-resistant adhesion Each sample was immersed in boiling water for two hours and then left indoors for one hour. After that, the coating was scratched in a certain direction with the outer edge of a 10 yen coin tilted at 45 degrees and the state of peeling of the coating was observed. The length of peeling that occurred at the interface was measured, the ratio to the scratch length (length of peeling that occurred / scratch length×100%) was calculated, and the evaluation was performed according to the following criteria. Results of ⊚ and ◯ were considered to be acceptable. ◎: No peeling at the interface between the topcoat and primer coatings, between the primer coating and chemical conversion coating, or between the chemical conversion coating and plating ○: Peeling of less than 10% occurred at the interface between the topcoat and primer coating, the interface between the primer coating and chemical conversion coating, or the interface between the chemical conversion coating and plating. ×: Peeling of 10% or more occurred at the interface between the topcoat film and the primer film, the interface between the primer film and the chemical conversion coating, or the interface between the chemical conversion coating and the plating.

[0082] [Table 1]

[0083] From the results in Table 1, it can be seen that each sample of the present invention was evaluated as ◎◎ to ○ for the corrosion resistance of the bent part, the corrosion resistance of the cut end, the adhesion at the bent part, and the scratch adhesion, and was excellent in all respects. Furthermore, it can be seen that when the base plated steel sheet was a Zn-55%Al plated steel sheet with improved workability by heat treatment (samples 23 and 24), the corrosion resistance of the bent part was particularly excellent, and when the base plated steel sheet was a hot-dip Al-Zn alloy plated steel sheet with a composition of Zn-55%Al-4%Mg-2%Si with improved corrosion resistance by adding Mg during plating (samples 25 and 26), the corrosion resistance of the cut end was particularly excellent. On the other hand, each sample in the comparative examples was outside the scope of the present invention in terms of the plating type, chemical conversion coating, or primer coating, but was marked △ or × in either the corrosion resistance of the bent portion, the corrosion resistance of the cut end, the adhesion at the bent portion, or the scratch adhesion, indicating that there were problems with performance. Samples 49 and 50 used chromate compounds in the chemical conversion coating and primer, and the coating used an environmentally hazardous substance, which resulted in problems with environmental friendliness and safety. [Industrial Applicability]

[0084] According to the present invention, it is possible to provide a coated steel sheet which has good adhesion between a chemical conversion coating and a primer coating and which has excellent corrosion resistance in processed portions and cut edges, in particular, on a hot-dip Al-Zn-plated steel sheet containing 50 mass % or more of Al, from which excellent corrosion resistance can be expected.

Claims

1. a hot-dip Al-Zn plated steel sheet having a plating layer having a composition containing 50 to 60 mass% Al, 1 to 3 mass% Si, and optional added components: 0 to 6 mass%, with the balance being Zn and unavoidable impurities; a chemical conversion coating film that does not contain a chromate-based compound and is formed on at least one surface of the hot-dip Al-Zn-plated steel sheet; a primer coating film that does not contain a chromate-based compound and is formed on the chemical conversion coating film; A topcoat coating film formed on the primer coating film; A coated steel sheet comprising: the chemical conversion coating contains a resin component and an inorganic compound, the resin component containing 30 to 54 mass% of an epoxy resin having a bisphenol skeleton, and the inorganic compound containing 46 to 70 mass% in total of vanadium oxide, zirconium oxide, and a fluorine compound, The primer coating film contains a resin component and an inorganic compound, and contains, as the resin components, a total of 40 to 88 mass% of an epoxy resin (e) having a urethane bond and a polyester resin (p), the content of the epoxy resin (e) and the polyester resin (p) being in a mass ratio of (e):(p)=80:20 to 60:40, and contains, as the inorganic compounds, 4 to 20 mass% of a vanadium compound, 4 to 20 mass% of a phosphoric acid compound, and 4 to 20 mass% of magnesium oxide. A coated steel sheet.

2. The coating weight of the chemical conversion coating is 0.025 to 0.5 g / m 2 2. The coated steel sheet according to claim 1, wherein the thickness of the primer coating film is 3 to 10 μm or more.

3. 3. The coated steel sheet according to claim 1, wherein a content (e1% by mass) of the epoxy resin having a urethane bond (e) in the primer coating film and a content (e2% by mass) of the epoxy resin having a bisphenol skeleton in the chemical conversion coating film satisfy a relationship of e1 / e2 = 0.7 to 1.

5.

4. 3. The coated steel sheet according to claim 1, wherein the chemical conversion coating contains, as the inorganic compounds, 2 to 10 mass% of the vanadium oxide, 36 to 60 mass% of the zirconium oxide, and 0.5 to 5 mass% of the fluorine compound, calculated as fluorine atoms.

5. The micro Vickers hardness (JIS Z2244:2009) of the plating film is 60 to 100HV 0.01 The coated steel sheet according to claim 1 or 2, characterized in that

6. The coated steel sheet according to claim 1 or 2, characterized in that the plating layer contains 1 to 5 mass % of Mg as the optional added component.

Citation Information

Patent Citations

  • Coated zn-al alloy plated steel sheet excellent in corrosion resistance

    JP2005169765A

  • Resin-coated metal sheet with excellent processing, welding and corrosion resistance properties, and finished piece and production process using the resin-coated metal sheet

    JP2006035842A

  • Coating material composition with excellent corrosion resistance

    JP2008291162A

  • Metal surface treatment composition

    JP2009127057A

  • Undercoat paint composition excellent in corrosion resistance

    JP2012012497A